Analisis Produktivitas Alat Berat Pada Pekerjaan Pengaspalan Jalan Matang Seping - Pelita Kabupaten Aceh Tamiang - Agusti, Eddy; Rajib Muammar; Iqbal (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Road infrastructure plays a vital role in supporting economic growth and facilitating community mobility. Matang Seping Village in Aceh Tamiang Regency suffers from severely damaged roads, hindering the distribution of agricultural and fishery products. To address this issue, a road paving project on the Matang Seping–Pelita route was carried out, requiring careful planning and efficient use of heavy equipment. This study aims to analyze the utilization and productivity of heavy equipment used in the road paving project. The analysis focuses on identifying the types of heavy equipment employed, calculating productivity based on the 2023 guidelines from the Ministry of Public Works and Public Housing (PUPR), and determining the number and operational duration of each equipment unit. The equipment used for the prime coat work includes a compressor and asphalt sprayer, while the base course layer (Asphalt Concrete-Base Course) uses a dump truck, asphalt finisher, tandem roller, and pneumatic tire roller. The results show varied productivity levels, with the asphalt sprayer reaching 13,695 liters/hour and the asphalt finisher 134.46 tons/hour. All equipment was operated over two days, with quantities adjusted to project needs, including 12 dump trucks to ensure the smooth implementation of fieldwork.